The Genital Tract Virulence Factor pGP3 Is Essential for Chlamydia muridarum Colonization in the Gastrointestinal Tract - Shao, Lili (Infect Immun, 2017)
The cryptic plasmid is essential for Chlamydia muridarum dissemination from the genital tract to the gastrointestinal (GI) tract. Following intravaginal inoculation, a C. muridarum strain deficient in plasmid-encoded pGP3 or pGP4 but not pGP5, pGP7, or pGP8 failed to spread to the mouse gastrointestinal tract, although mice infected with these strains developed productive genital tract infections. pGP3- or pGP4-deficient strains also failed to colonize the gastrointestinal tract when delivered intragastrically. pGP4 regulates pGP3, while pGP3 does not affect pGP4 expression, indicating that pGP3 is critical for C. muridarum colonization of the gastrointestinal tract. Mutants deficient in GlgA, a chromosome-encoded protein regulated by pGP4, also consistently colonized the mouse gastrointestinal tract. Interestingly, C. muridarum colonization of the gastrointestinal tract positively correlated with pathogenicity in the upper genital tract. pGP3-deficient C. muridarum strains did not induce hydrosalpinx or spread to the GI tract even when delivered to the oviduct by intrabursal inoculation. Thus, the current study not only has revealed that pGP3 is a novel chlamydial colonization factor in the gastrointestinal tract but also has laid a foundation for investigating the significance of gastrointestinal Chlamydia.